2012
DOI: 10.1158/1940-6207.capr-11-0469
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Trial of Lyophilized Strawberries in Patients with Dysplastic Precancerous Lesions of the Esophagus

Abstract: Dysplasia is a histologic precursor of esophageal squamous cell carcinoma (SCC). We previously showed that dietary freeze-dried, or lyophilized, strawberry powder inhibits N-nitrosomethylbenzylamine-induced SCC in the rat esophagus. On the basis of this observation, we conducted a randomized (noncomparative) phase II trial in China to investigate the effects of two doses of freeze-dried strawberries in patients with esophageal dysplastic lesions in a high-risk area for esophageal cancer. We randomly assigned 7… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 37 publications
2
76
1
Order By: Relevance
“…1, Supplementary Table S5). In other clinical trials with oral administration of berries, BRBs have been shown to be well tolerated and exert protective effects in patients with colorectal cancer (14) and Barrett's esophagus (15), and strawberries regress mild dysplastic esophageal lesions that are precursors to squamous cell carcinoma (25). Accordingly, we anticipated that oral BRBs plus BRB suppositories could be more effective than suppositories alone in regressing polyps in patients with FAP.…”
Section: Discussionmentioning
confidence: 99%
“…1, Supplementary Table S5). In other clinical trials with oral administration of berries, BRBs have been shown to be well tolerated and exert protective effects in patients with colorectal cancer (14) and Barrett's esophagus (15), and strawberries regress mild dysplastic esophageal lesions that are precursors to squamous cell carcinoma (25). Accordingly, we anticipated that oral BRBs plus BRB suppositories could be more effective than suppositories alone in regressing polyps in patients with FAP.…”
Section: Discussionmentioning
confidence: 99%
“…Preneoplastic changes, as well as changes in the expression of inflammatory and angiogenic biomarkers, closely resemble changes observed in human esophageal SCC. Lesions follow the progression sequence from normal>hyperplasia>mild, moderate, and severe dysplasia>papilloma>to esophageal SCC (4,29). Dysregulated changes in inflammatory biomarker expression, namely COX-2, iNOS, and NF-kB, have been reported during tumor development in this model (6,7,9,29,30).…”
Section: Introductionmentioning
confidence: 70%
“…Lesions follow the progression sequence from normal>hyperplasia>mild, moderate, and severe dysplasia>papilloma>to esophageal SCC (4,29). Dysregulated changes in inflammatory biomarker expression, namely COX-2, iNOS, and NF-kB, have been reported during tumor development in this model (6,7,9,29,30). The present study evaluates whether BRBs, their component ACs, and PCA alter immune cell trafficking within the esophagi of NMBA-treated F-344 rats, and whether these changes are associated with inhibition of tumorigenesis.…”
Section: Introductionmentioning
confidence: 70%
“…To test these hypotheses, two large chemoprevention trials were implemented-one in the general population [65] and the other in patients with high-risk precursor lesions [66]-to test a range of nutritional interventions, but they delivered essentially null results [67, 68••]. When these findings were placed alongside null findings from other trials [69,70], enthusiasm for further nutritional interventions for ESCC was tempered. More recently, a small number of cohort studies conducted in both Western and Chinese populations have reported that diets with high intakes of fruits or vegetables, or with indices of high dietary quality, are associated with reduced risks of ESCC [47][48][49]71].…”
Section: Dietmentioning
confidence: 99%